If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 2x Solving 23 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 23 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 23 + -2x = 0 Add '-23' to each side of the equation. 23 + -23 + -2x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -2x = 0 + -23 -2x = 0 + -23 Combine like terms: 0 + -23 = -23 -2x = -23 Divide each side by '-2'. x = 11.5 Simplifying x = 11.5
| (2y-3)(y+5)=0 | | y=1.5x-1 | | 25x+3=5(5x+1)-x+4 | | x+3x^2-2=0 | | y=-3.5x-2 | | y=3.5x-1 | | y=6x^2-9 | | (-8x)-4=36 | | 5=3x-4 | | 2=4m+8 | | -19=3x-4 | | 3x+8x=-132 | | (2x+-65)=15x | | (2x+-65)=15 | | 4x+6=2x+16 | | 124x=7 | | 1(x-1)=-4x+34 | | 2(x+3)+30=-4x | | 7(x-2)=2x+26 | | (4x+78)=30x | | 5x^2-6x+21=0 | | y^2-4x^2-2x+3y+1=0 | | 2w^2+4w-170=w^2+3w | | w^2+w-170=0 | | (2x+-14)=9x | | 3(x+3)+26=-4x | | 150+x+x=1500 | | 3(2x+-14)=9x | | 3(x+18)=-3(x-12) | | 3X+12=180 | | 105=(x+2)x*3 | | 9x^4-18x^3+2x^2+7x-2=0 |